Influence of external and internal auditors on key audit matters (KAMs) reporting in Thailand - Kriengkrai Boonlert-U-Thai; Muttanachai Suttipun (Cogent Business & Management, 2023)
The study aims to investigate the level and pattern of Key Audit Matters (KAMs) reporting, and to examine the influence of external auditor and audit committee characteristics on KAMs reporting of listed companies in the Stock Exchange of Thailand (SET). Using 200 listed companies of the SET as samples used in this study, the KAMs reporting is measured by the content analysis in auditor's report, while external auditor characteristics are proxied by audit type, audit fees, female auditor, and auditor rotation. Audit committee characteristics are proxied by audit committee member, proportion of financial expertise, meeting frequency, and member independence. Descriptive analysis, correlation matrix, and balanced panel analysis are used to analyze the data. The average level of KAMs reporting is 1.96 issues. The KAMs reporting shows a declining trend during year 2017 to 2020, while audit fees have increased during period being study. Finally, the study finds that the KAMs reporting is positively influenced by audit fees, female auditor, audit committee size, and meeting frequency. However, the study finds that high proportion of financial expertise audit committee reduces the level of KAMs reporting. The legitimacy theory can be demonstrated to explain the influence of external auditor and audit committee on KAMs reporting. Shareholders, creditors, and investors can use KAMs reporting as important information for their decision-making.
Keywords: 650; external auditor; internal auditor; KAMs reporting; Thailand